ANALYSIS OF SOLVENCY VARIABLES IN MODERATING THE EFFECT OF MACROECONOMIC VARIABLES ON THIRD PARTY FUNDS (CASE STUDY ON BCA SYARIAH FOR THE 2013-2022 PERIOD) - Ainiah, Zumrotul; Bawono, Anton (Economic and Science Faculty of Islamic State University, 2023)
This research was conducted to analyze solvency ability in moderating the effect of macroeconomic factors on third party funds at BCA Syariah for the 2013-2022 period. This type of research is quantitative research using MRA or Moderated Regression Analysis as an analytical tool. The data used in this study is secondary data with s monthly period time series pattern obtained from financial reports issued by BCA Syariah. This software for data analysis used in this study is Eviews 10. The results obtained are that inflation has no effect on third party funds, the BI Rate has no effect on third party funds, the money supply has a positive and significant effect on third party funds, gross domestic product has no influence on third party funds, solvency can moderate the relationship of currency exchange rates to third party funds, and solvency can moderated the relationship of the joint stock price index to third party funds.